Analisis Dan Perancangan Sistem Informasi Manajemen Aset Pada SMA Negeri 4 Kota Jambi - Varezki, Febby; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2021)
SMA Negeri 4 Jambi City is one of the high schools in Jambi province with several majors. Asset management at SMA N 4 Jambi City is done manually and using Microsoft Office Excel so that the performance of the asset management system is still not optimal. One way that management can be optimized is by the use of information systems. The asset management research was carried out at the asset planning, asset procurement, asset receipt and asset placement stages. This research produces a prototype system that describes the functional planning, procurement, receipt and placement of assets in SMA N 4 Jambi City. The method used is an object-oriented approach using UML (unified modeling language), namely use case diagrams, class diagrams and activity diagrams. This research produces a prototype that can be studied further to produce an asset management information system that can be implemented at SMA N 4 Jambi City.